2022
DOI: 10.1007/s11274-022-03496-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of solid-state fermented cassava roots (Manihot esculenta Crantz) and its application in broiler feed formulation

Abstract: The biochemical parameters of solid-state fermented peeled and unpeeled cassava roots (Manihot esculenta Crantz) and their application in broiler feed formulations were investigated. Fermentation occurred at room temperature for 72 h (pH 3-9). The samples utilized for five (5) broiler starter feeds were labeled: control, unfermented unpeeled cassava (UUC), unfermented peeled cassava (UPC), fermented unpeeled cassava (FUC), and fermented peeled cassava (FPC). Formulations were made by substituting fermented/non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…When compared to the control group, the untreated Diabetes mellitus group's creatinine level was shown to be considerably higher (Figure 2). These findings concur with those of Usmanet al 52 , Baragob 53 , Egbune et al 56 A little increase in creatinine was seen in the periodontitis group, but it was not statistically different from the control group. Vasconcelos et al 54 and Souza et al 55 reported comparable results.…”
Section: Effects Of Nigella Sativa Oil On Serum Urea and Creatinine L...supporting
confidence: 92%
“…When compared to the control group, the untreated Diabetes mellitus group's creatinine level was shown to be considerably higher (Figure 2). These findings concur with those of Usmanet al 52 , Baragob 53 , Egbune et al 56 A little increase in creatinine was seen in the periodontitis group, but it was not statistically different from the control group. Vasconcelos et al 54 and Souza et al 55 reported comparable results.…”
Section: Effects Of Nigella Sativa Oil On Serum Urea and Creatinine L...supporting
confidence: 92%
“…Our study (Egbune et al, 2023a(Egbune et al, , 2024Eedom et al, 2023) introduces a feasible method for L-lysine production using agricultural by-products such as palm kernel cake, soybean cake, groundnut cake, and wheat offal. Solid-state fermentation with C. glutamicum ATCC 13032 resulted in the production of L-lysine from these agricultural by-products (Figure 2).…”
Section: Production Of L-lysine By Solid-state Fermentationmentioning
confidence: 99%
“…Maintaining controlled environmental conditions, including temperature and humidity, is crucial for optimizing microbial growth and L-lysine synthesis. The process emphasizes the strategic use of local agricultural byproducts, contributing to efficiency and sustainability (Egbune et al, 2023a, Ezedom et al, 2023Egbune et al, 2024). Downstream processing involves extracting and purifying lysine from the fermented solid substrate using solvents and various techniques, such as ion exchange chromatography, highlighting the importance of a well-defined production pathway for economic viability and sustainability (Sinha et al, 2022;Ewing et al, 2022).…”
Section: Solid-state Fermentation Process Used For L-lysine Productio...mentioning
confidence: 99%
“…The optimal environment for simulated strain growth was maximized by selecting different solid fermentation substrates to provide nitrogen sources, carbon sources, and nutrients. [ 157 ] Thus, SSF has wide applications in the production of enzymes, industrial chemicals, biofuels, and so on. [ 158‐160 ] Currently, some filamentous fungi consortium systems can achieve co‐metabolic activity under optimal co‐culture conditions for SSF, efficiently utilizing the substrate and thus improving product purities.…”
Section: Solid‐state Fermentation: Tradition Innovation and Futurementioning
confidence: 99%